Evaluation of the effect of the carrier of polymorphic variants of the SLCO1B1 gene on efficacy and safety in patients during treatment with statins - N. A. Rumyantsev; Yu. V. Olefir; V. G. Kukes (Безопасность и риск фармакотерапии, 2018)
The number of patients receiving statins is increasing every year. Considering the need for life-long intake of drugs of this group, the problem of improving safety and efficacy of their use becomes especially important. There is a large amount of data on the influence of various genetic factors on the safety of statins and the frequency of side effects peculiar to this group of drugs, such as statin-induced myopathy and rhabdomyolysis. The article presents the long-term results of a study devoted to the evaluation of the effect of the carriage of various polymorphic variants of SLCO1B1 on the safety and efficacy of statin therapy in terms of long-term treatment outcomes.